Association between prognostic factors and the clinical deterioration of preterm neonates with necrotizing enterocolitis - Ibrohim, Ibnu Sina (Springer, 2022)
Necrotizing enterocolitis (NEC) is responsible for most morbidity and mortality in neonates. Early recognition of the clinical deterioration in newborns with NEC is essential to enhance the referral and management and potentially improve the outcomes. Here, we aimed to identify the prognostic factors and associate them with the clinical deterioration of preterm neonates with NEC. We analyzed the medical records of neonates with NEC admitted to our hospital from 2016 to 2021. We ascertained 214 neonates with NEC. The area under the receiver operating characteristic (ROC) curve and cut-off level of age at onset, C-reactive protein (CRP), leukocyte count, and platelet count for the clinical deterioration of preterm neonates with NEC was 0.644 and 10.5 days old, 0.694 and 4.5 mg/L, 0.513 and 12,200/mm 3 , and 0.418 and 79,500/mm 3 , respectively. Late-onset, history of blood transfusion, thrombocytopenia, and elevated CRP were significantly associated with the clinical deterioration of neonates with NEC (p = < 0.001, 0.017, 0.001, and < 0.001, respectively), while leukocytosis, gestational age, and birth weight were not (p = 0.073, 0.274, and 0.637, respectively). Multivariate analysis revealed that late-onset and elevated CRP were strongly associated with the clinical deterioration of neonates with NEC, with an odds ratio of 3.25 (95% CI = 1.49–7.09; p = 0.003) and 3.53 (95% CI = 1.57–7.95; p = 0.002), respectively. We reveal that late-onset and elevated CRP are the independent prognostic factor for the clinical deterioration of preterm neonates with NEC. Our findings suggest that we should closely monitor preterm neonates with NEC, particularly those with late-onset of the disease and those with an elevated CRP, to prevent further clinical deterioration and intervene earlier if necessary.